Increased Serpina3n release into circulation during glucocorticoid‐mediated muscle atrophy. Issue 5 (10th July 2018) - Gueugneau, Marine; d'Hose, Donatienne; Barbé, Caroline; de Barsy, Marie; Lause, Pascale; Maiter, Dominique; Bindels, Laure B.; Delzenne, Nathalie M.; Schaeffer, Laurent; Gangloff, Yann‐Gaël; Chambon, Christophe; Coudy‐Gandilhon, Cécile; et al.
Abstract: Background: Glucocorticoids (GC) play a major role in muscle atrophy. As skeletal muscle is a secretory organ, characterization of the muscle secretome elicited by muscle atrophy should allow to better understand the cellular mechanisms and to identify circulating biomarkers of this condition. Our project aimed to identify the changes in the muscle secretome associated with GC‐induced muscle atrophy and susceptible to translate into circulation. Methods: We have identified the GC‐induced changes in the secretome of C2 C12 muscle cells by proteomic analysis, and then, we have determined how these changes translate into the circulation of mice or human subjects exposed to high concentrations of GC. Results: This approach led us to identify Serpina3n as one of the most markedly secreted protein in response to GC. Our original in vitro results were confirmed in vivo by an increased expression of Serpina3n in skeletal muscle (3.9‐fold; P < 0.01) and in the serum (two‐fold; P < 0.01) of mice treated with GC. We also observed increased levels of the human orthologue Serpina3 in the serum of Cushing's syndrome patients compared with healthy controls matched for age and sex ( n = 9/group, 2.5‐fold; P < 0.01). An increase of Serpina3n was also demonstrated in muscle atrophy models mediated by GC such as cancer cachexia (four‐fold; P < 0.01), sepsis (12.5‐fold; P < 0.001), or diabetes (two‐fold; P < 0.01). In contrast, levels of Serpina3n both in skeletal muscle and in the circulation were reduced in several models of muscle hypertrophy induced by myostatin inhibition ( P < 0.01). Furthermore, a cluster of data suggests that the regulation of muscle Serpina3n involves mTOR, an essential determinant of the muscle cell size. Conclusions: Taken together, these data suggest that Serpina3n may represent a circulating biomarker of muscle atrophy associated to GC and, broadly, a reflection of dynamic changes in muscle mass.